Comparative Viability Analysis of Monolayer Cell Suspension and Multicellular Tumor Spheroids as an In-vitro Tumor Model - Aziz Ur Rahman,; Islam, Zahoor; Abid Ullah,; Irfan, Muhammad; Ahmad, Saeed; Rashid, Sheikh Abdur (Indus Journal of Bioscience Research, 2025)
Background: Monolayer cell suspension has been used as an in-vitro model for investigating cells characteristics, drug penetration, and tissue research. 3-D multicellular tumor spheroids (3-D MCTS) have attained focus of researchers from the last three decades as a more valuable tool to study tumor biology. The superiority of MCTS has been elucidated here along with the effect of disaggregated spheroids. Method: The cellular differentiating fluorophores; calcein-AM and Propidium Iodide (PI) have been exploited for cells viability characteristics, where calcein-AM penetrate viable proliferating cells only, PI penetrate dead cells only, while viable hypoxic cell remains unstained and are resistant to penetration of either fluorophore. Fluorophores uptake in 3, 5, and 7-day old intact spheroids, disaggregated spheroids, and monolayer cell suspension has been investigated. Results: The Calcein-AM stained cells and unstained cells fraction in intact, disaggregated, and monolayer cell suspension was statistically non-significant (ANOVA p = 0.072 and 0.411 respectively), while the PI-stained cells fraction showed statistical significance (ANOVA, p = 0.012). PI-stained cells fraction was greater in intact spheroids followed by disaggregated spheroids with a minimum fraction in monolayer cell suspension. This effect could be due to compact nature, microenvironment, and deficient drainage in spheroids mimicking in-vivo tumor. Conclusion: The disaggregated spheroids serve as intermediate between intact spheroids and monolayer cell suspension. The intact spheroids possess superiority over monolayer cell suspension being more compact, and resemblance to in-vivo tumors to elucidate tumor biology.